INTRA-ARTERIAL CHEMOTHERAPY AND ITS SIGNIFICANCE IN THE TREATMENT OF OROPHARYNGEAL CARCINOMA - Simek, Jiri; Ehrmann, Jiri; Pazdera, Jindrich (Biomedical papers, 2007)
Background: In complex therapeutic algorithms for cancer, regional intra-arterial chemotherapy is usually used as an adjuvant and placed in the beginning of treatment. Clinical experience however shows that the achieved remission of malignant tumour illness after non-adjuvant chemotherapy is only temporary and short-lived. The illness progresses relatively quickly if the patient receives no further treatment and most clinical studies have not found any significant increase in life expectancy in oncological patients treated with this method. The question remains to what extent the poor results are due to the treatment method and its position in the therapeutic algorithm, and to what extent they are due to imperfect knowledge of molecular tumour genetics or inappropriate choice of the neoadjuvant intra-arterial chemotherapy Methods: We compared preliminary results of immunohistochemical examinations (detection and analysis of expression of proteins Ku 70, STAT 1,3,5 which take part in the regulation of cell cycle apoptosis and repair of damaged DNA, carried out before and after chemotherapy, suggest that depending on the effects of neoadjuvant intra-arterial chemotherapy and patient's survivance. Results and Conclusion: An overview of intra-arterial neoadjuvant chemotherapy of head and neck is presented. Knowledge of cell cycle processes, especialy apoptosis and repair of damaged DNA, could significantly influence the choice of the therapeutic algorithm and therapeutical effect.
Keywords: Oropharyngeal carcinoms/Intra-arterial chemotherapy